Independensi Entrepeneur With Digital Marketing - Julita Julita; Nel Arianty (AIBPM Publisher, 2019)
Digital marketing is a digital marketing technology implementation. The role of digital marketing can attract consumers and direct them to a blend of electronic communication and traditional communication. Digital Marketing provides opportunities for small businesses to attract new customers and reach existing customers more efficiently. This research aims to determine the independence of the entrepreneur with the application of digital marketing in SMEs. The respondent of this research was the SME actors in Lubuk Pakam district of Deli Serdang Regency. This research sample of 40 SMEs, sample withdrawal in this study using Probability Sampling technique. The analytical techniques used in this study are quantitative data analysis, i.e. testing and analyzing data by calculation of numbers and then drawing conclusions from multiple linear regression and hypothesis testing through test (Test-T), simultaneous test (F-test) and coefficient of determination, in practice the data processing of this research is not processed manually, but using SPSS statistical software. The results showed that there was an influence on entrepreneur independence with digital marketing. Because of the high entrepreneur's independence rate affects digital marketing